SHAKESPEARE AND GAME OF THRONES - Wilson, Jeffrey R. (Jeffrey Robert), 1982- ([S.l.] : ROUTLEDGE, 2020)
It is widely acknowledged that the hit franchise Game of Thrones is based on the Wars of the Roses, a bloody fifteenth-century civil war between feuding English families. In this book, Jeffrey R. Wilson shows how that connection was mediated by Shakespeare, and how a knowledge of the Shakespearean context enriches our understanding of the literary elements of Game of Thrones. On the one hand, Shakespeare influenced Game of Thrones indirectly because his history plays significantly shaped the way the Wars of the Roses are now remembered, including the modern histories and historical fictions George R.R. Martin drew upon. On the other, Game of Thrones also responds to Shakespeare's first tetralogy directly by adapting several of its literary strategies (such as shifting perspectives, mixed genres, and metatheater) and tropes (including the stigmatized protagonist and the prince who was promised). Presenting new interviews with the Game of Thrones cast, and comparing contextual circumstances of composition--such as collaborative authorship and political currents--this book also lodges a series of provocations about writing and acting for the stage in the Elizabethan age and for the screen in the twenty-first century. An essential read for fans of the franchise, as well as students and academics looking at Shakespeare and Renaissance literature in the context of modern media.
OCLC-licensed vendor bibliographic record.
Keywords: Martin, George R. R; Shakespeare, W. M. -- Influence; Game of thrones (Television program); History on television; Literature and history; Great Britain -- History -- Wars of the Roses, 1455-1485 -- Literature and the war; LITERARY CRITICISM / General